New risk score of the early period after spontaneous subarachnoid hemorrhage: For the prediction of delayed cerebral ischemia. (12th August 2019) - Fang, Yuan‐Jian; Mei, Shu‐Hao; Lu, Jia‐Nan; Chen, Yi‐Ke; Chai, Zhao‐Hui; Dong, Xiao; Araujo, Camila; Reis, Cesar; Zhang, Jian‐Min; Chen, Sheng
Abstract: Background and Purpose: The aim of this study is to identify the early predictors for delayed cerebral ischemia (DCI) and develop a risk stratification score by focusing on the early change after aneurysmal subarachnoid hemorrhage (aSAH). Methods: The study retrospectively reviewed aSAH patients between 2014 and 2015. Risk factors within 72 hours after aSAH were included into univariable and multivariable logistic regression analysis to screen the independent predictors for DCI and to design a risk stratification score. Results: We analyzed 702 aSAH patients; four predictors were retained from the final multivariable analysis: World Federation of Neurosurgical Societies scale (WFNS; OR = 4.057, P < .001), modified Fisher Scale (mFS; OR = 2.623, P < .001), Subarachnoid Hemorrhage Early Brain Edema Score (SEBES; OR = 1.539, P = .036), and intraventricular hemorrhage (IVH; OR = 1.932, P = .002). According to the regression coefficient, we created a risk stratification score ranging from 0 to 7 (WFNS = 3, mFS = 2, SEBES = 1, and IVH = 1). The new score showed a significantly higher area under curve (0.785) compared with other scores ( P < .001). Conclusion: The early DCI score provides a practical method at the early 72 hours after aSAH to predict DCI.